IDENTIFIKASI 11-NOR-Δ 9 -TETRAHYDROCANNABINOL-9-CARBOXYLIC ACID (THC-COOH) DALAM SAMPEL URIN MENGGUNAKAN INSTRUMEN GAS CHROMATOGRAPHY-MASS SPECTROMETRY (GC-MS) - Utami, Maisari; Abdushshobir, Muhammad Fadhil; Tanti, Tanti (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
“Narkoba” is known as an narcotics, psychotropics, and other addictive substances. Drugs are substances that can affect brain function and often cause dependence. One type of drug that is common in Indonesia is marijuana. Marijuana is a psychotropic that contains tetrahydrocannabinol (THC). When THC enters the human body, it will undergo a metabolic process and produce metabolites in the form of 11-nor-δ 9 -tetrahydrocannabinol-9-carboxylic acid (THC-COOH) which are then excreted in the urine. Urine identification can be used to prove someone's use of marijuana. Identification is carried out using urine from the National Narcotics Agency's Narcotics Laboratory Center to confirm the presence of THC-COOH using a Gas Chromatography-Mass Spectrometer (GC-MS). Urine identification is carried out with a preliminary rapid test and a confirmation test using a GC-MS instrument. The identification results showed that the urine was positive for THC-COOH.